Assessment of prevalence and distribution of congenital missing teeth among patients visiting tertiary care hospital: A radiographic study - Khushboo Arif; Vinay Kumar Gupta; Gaurav Mishra; Sumit Kumar; Atrey Pai Khot; Sonal Bhatia; Ranjit kumar Patil; Abhishek Singh; Mohammad Imran Khan (Elsevier, 2024)
Introduction: Dental Agenesis is the usual developmental dental anomaly involving both primary and permanent dentition but most commonly it affects the permanent teeth. Genetic mutations in genes like MSX, PAX9,TGFA and AXIN2 are the likely primary contributors to tooth agenesis. Identifying the prevalence and distribution of congenital missing teeth allows for early detection and intervention which is crucial for preventing or mitigating potential dental issues that may arise due to missing teeth. Aim & objectives: To assess the prevalence and distribution of congenitally missing teeth across different quadrants of the jaw among patients visiting to the Dental out patient department at Tertiary Care Centre of Lucknow city. Material & method: A Questionnaire and orthopantomogram based cross-sectional study was conducted on both male and female patients aged between 15 and 30 years, coming for evaluation of their dental health problems to the hospital. Written informed consent was obtained. Results: The overall prevalence of CMT was found to be 33.3 %. The significant difference was observed in proportion of CMT between Maxilla and Mandible sites (p = 0.008). Higher prevalence was in females compared to males for both maxillary and mandibular congenital missing teeth. (p = 0.020). Conclusion: The most common CMT were third molars followed by lateral incisors. The insights derived from the study would aid dental professional in gaining a deeper comprehension of tooth agenesis.